Fluid and sodium balance of elite wheelchair rugby players - Black, K. E.; Huxford, J.; Perry, T. L.; Brown, R. C. (International Journal of Sport Nutrition and Exercise Metabolism, 2013)
Blood sodium concentration of tetraplegics during exercise has not been investigated. This study aimed to measure blood sodium changes in relation to fluid intakes and thermal comfort in tetraplegics during wheelchair rugby training. Twelve international male wheelchair rugby players volunteered, and measures were taken during 2 training sessions. Body mass, blood sodium concentration, and subjective thermal comfort using a 10-point scale were recorded before and after both training sessions. Fluid intake and the distance covered were measured during both sessions. The mean (SD) percentage changes in body mass during the morning and afternoon training sessions were +0.4%1 (0.65%) and +0.69% (1.24%), respectively. There was a tendency for fluid intake rate to be correlated with the percentage change in blood sodium concentration (p = .072, r2 = .642) during the morning training session; this correlation reached significance during the afternoon session (p = .004, r2 = .717). Fluid intake was significantly correlated to change in thermal comfort in the morning session (p = .018, r2 = .533), with this correlation showing a tendency in the afternoon session (p = .066, r2 = .151). This is the first study to investigate blood sodium concentrations in a group of tetraplegics. Over the day, blood sodium concentrations significantly declined; 2 players recorded blood sodium concentrations of 135 mmol/L, and 5 recorded blood sodium concentrations of 136 mmol/L. Excessive fluid intake as a means of attenuating thermal discomfort seems to be the primary cause of low blood sodium concentrations in tetraplegic athletes. Findings from this study could aid in the design of fluid-intake strategies for tetraplegics.